A Review of "Options in Management of Trauma to the Esophagus" (1982) "Submitted for the Literary Festschrift in Honor of J. David Richardson, MD". Issue 2 (February 2021) - Cheadle, Gerald A; Cheadle, William G
This article is an update of a paper which Dave Richardson and I published in 1982, and serves as both an update of management of esophageal injuries and as a lasting tribute to my mentor and hero J. David Richardson.